Digital technologies in physical education of students: experience using a mobile application - Kiryanova, L.A.; Sidorenko, I.S. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to examine the impact of using mobile applications and wearable devices on students’ motivation for physical education classes. Methods and structure of the study. An anonymous survey was conducted among students to determine their attitude towards such technologies in the educational environment, the frequency of their use, as well as their influence on motivation for physical activity. Results and conclusions. The results showed a positive dynamic in students’ engagement with an active lifestyle when using digital technologies (activity trackers).